ANALISIS DISTRIBUSI SPASIAL PEMBUANGAN SAMPAH ILEGAL DI JALAN PROF. DR. HERMAN YOHANES PENFUI - Mamulak, Paulus; Pamungkas, Bella Theo Tomi; Hasan, Muhammad Husain (Jurnal Geografi, 2023)
The increasing population of Kupang City has resulted in an increasing volume of waste being managed so that additional landfills will always be needed. An increase in the number of piles of uncontrolled waste will eventually make the capacity of landfills reach the maximum limit or overload. Dr. Herman Yohanes Penfui, 2) to find out the strategy for determining the location of legal waste disposal sites on Jalan Prof. Dr. Herman Yohanes Penfui. The data analysis technique used in this study is descriptive analysis and is presented in the form of output maps, nearest neighbor analysis to find out the distribution pattern and analysis of the suitability of TPS presence to determine the feasibility of TPS. In this study, the research sample consisted of 2 Penfui Village officials, and 5 people from the community, so the total number of respondents consisted of 7 people. Data collection was carried out by means of observation, interviews and documentation. The results showed that 1) there were 8 illegal TPS locations which were very close together, so this greatly affected the environmental conditions in the research location area, andthe pattern of distribution of TPS in the research location was clustered, 2) Based on the results carried out by buffering analysis using the ArcGIS 10.4 application related to the strategic location of temporary waste disposal sites in accordance with predetermined conditions and directions from several sources' opinions as a reference for determining the legal TPS location strategy in the study there were 30 TPS PS recommendations needed in the research location area.